The role of social protection for the elderly caring for HIV/AIDS orphans in Malawi - Ngwira, Marumbo Prisca (My University, 2016)
The HIV and AIDS pandemic has increased the numbers of orphans globally. The severity of the problem is greater in developing countries, especially in Sub Saharan Africa. In Malawi, as in many other developing countries, grandparents have stepped in and have embraced the role left by the deceased parents, seeing the orphans through school, providing food, clothing and shelter for them, even where the grandparents themselves have no steady source of income. Despite the heavy burden placed on grandparents as a result of HIV and AIDS, limited attention has been given by governments, scholars and researchers to documenting in detail the challenges faced by the elderly who look after orphaned children. This study examined the challenges faced by elderly people looking after children orphaned by HIV and AIDS in Malawi using the Sustainable Livelihoods Framework (SLF). This framework looks at household needs and holistically categorises them in terms of social, financial, physical, natural health, and government policies. Following a qualitative approach, this study used a phenomenology approach in documenting the challenges facing the elderly in Malawi, with a special focus on the Rumphi and Zomba districts. The livelihood approach is part of rural development theories that has moved away from the conventional approaches towards development to holistic understanding of the relationship between poverty and economic development. The study also provided a case study on the role of social pensions in Lesotho. Social protection, which is part of social development, focuses on local community development with the emphasis not only on economic development, but also on improvement of health, education, environment and standard of living as critical contributors to sustainable development. This is seen as a medium that discourages dependency and promotes the participation of people in their own development. The aim was to profile social protection benefits for the elderly in Lesotho as an example so that insights could be drawn from the experience. The study used structured and semi-structured interviews and focus group discussions as tools to elicit information from grandparents, orphans, community leaders, teachers, local leaders and policy makers. The findings of the study indicate that the level of rural poverty in elderly headed households has increased due to the challenges resulting from the HIV and AIDS pandemic. The Sustainable Livelihoods Approach presented in this paper advocates that sustained development is only successful if it is based on evidence and understanding of household or community needs holistically and systematically. This study has highlighted five key elements required to understand the elderly households through the Sustainable Livelihoods Framework. Firstly, the evidence from this research challenges the SLF in that it does not take into account all key factors necessary to understanding the elderly households’ needs, As a result, this study proposes other necessary enhancements to the SLF, such as the role of cultural practices as part of social capital in supporting elderly livelihoods, especially where patrilineal and matrilineal family systems exist. Secondly, evidence from this study indicates that the notion of social capital that includes dependency on community networks as key in improving the general livelihood of societies has completely diminished due to community fatigue in relation to offering care and support. The study further reveals enhancements in the forms of social capital like belonging to “secret friendships” or being a member of the village banking scheme. However these social networks have limited elderly membership because of community perceptions that elderly members may not contribute much, be it financially or otherwise, hence the elderly are excluded from social networks. Thirdly, as a result of the many challenges faced by the elderly, this research has highlighted an increase in negative coping strategies in elderly households due to limited support from government and other stakeholders. Negative coping strategies in this regard include engaging in activities like casual labour (ganyu), selling alcohol, school dropouts, selling green maize and begging. The more the elderly adopt negative coping strategies, the more vulnerable they become over time. Fourthly, the livelihoods framework has been used in this study to provide a full understanding of situation of the elderly headed households. This approach provides a new dimension to this body of knowledge as it is used for the first time on elderly households. The research presents a foundation that will require future researchers to look at elderly households holistically and systematically within their context using this research as a guideline or as a point of reference. Finally, this research suggests a possible framework that would address the needs of the elderly, with a combination of the livelihoods framework as the analysis tool and the social pensions as the response mechanism for alleviating the burden on elderly headed households. Social pensions will act as a poverty cushion to the elderly members of the society to meet their needs in raising orphaned children. This research conclusively reinforces the role of social protection for supporting the elderly livelihoods. The researcher’s contribution to theory is embedded in the premises of integration of livelihoods frameworks as an analysis tool that provides an holistic picture of understanding elderly household challenges and needs. Social protection through social pensions can be an intervention for supporting the household challenges of the elderly. The combination of these two frameworks results in an holistic and systematic analysis of elderly livelihoods and subsequent support necessary to respond to their challenges.
A thesis submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy Final Submission June, 2015.
Keywords: Older people--Care--Malawi; Older people--Malawi--Social conditions; Orphans--Malawi; AIDS (Disease) in children--Malawi